2007
DOI: 10.1021/pr0700798
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Biomarker Proteins Released by Human Endometrial and Cervical Cancer Cells Using Two-Dimensional Liquid Chromatography/Tandem Mass Spectrometry

Abstract: Candidate biomarker proteins, including chaperonin 10 and pyruvate kinase, previously discovered and identified using mass-tagging reagents with multidimensional liquid chromatography and tandem mass spectrometry (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…A total of 56 CD antigens were detected among the HeLa cell proteins, accounting for nearly 25% of the glycoproteins identified (supplemental Table 2). The effectiveness of surface membrane enrichment from our results is comparable with other reported studies (38,(41)(42)(43)(44)(45). We also detected other classes of surface membrane proteins including GPI-anchored proteins.…”
Section: N-linked Glycosylation Sites Identified In the M Amurensis supporting
confidence: 91%
“…A total of 56 CD antigens were detected among the HeLa cell proteins, accounting for nearly 25% of the glycoproteins identified (supplemental Table 2). The effectiveness of surface membrane enrichment from our results is comparable with other reported studies (38,(41)(42)(43)(44)(45). We also detected other classes of surface membrane proteins including GPI-anchored proteins.…”
Section: N-linked Glycosylation Sites Identified In the M Amurensis supporting
confidence: 91%
“…[34][35][36][37] As a result, the screening for disease markers became one of the main topics in a large number of proteomic studies in the past decade. [38][39][40][41][42] In this study, we performed a proteomic analysis to investigate tumor-specific protein expression of human breast carcinoma tissues. Our results showed that proteins involved in antiapoptosis, cell motility, cell proliferation, glycolysis, protein folding, signal transduction, and other processes related to tumorigenesis were overexpressed in cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Acetone-precipitated GBM secretome proteins (50 lg) were digested with trypsin (Promega) using an established in-solution digestion protocol [13]. Peptides were separated by two-dimensional liquid chromatography with strong cation exchange being the first dimension, followed by reverse phase chromatography in the second dimension as previously published [14].…”
Section: Mass Spectrometry Analysis Of Gbm Secretomementioning
confidence: 99%